2014
DOI: 10.15640/jges.v2n2a2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Long-Term Trends In Vegetation Productivity Change Over the Bani River Basin in Mali (West Africa)

Abstract: Using time series of Normalized Difference Vegetation Index (NDVI) and rainfall data, we investigated historical vegetation productivity trends from 1982 to 2011 over the Bani River Basin in Mali. Statistical agreements between long-term trends in vegetation productivty, corresponding rainfall and rate of land cover change from Landsat time-series imagery was used to discern climate versus human-induced vegetation cover change. Spearman correlation was used to investigate the relationship between metrics of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Which is a non-parametric test that does not require normally distributed data for validity [ 65 ]. This test is widely used in studies of hydrological, climatological and NDVI time series [ 65 , 66 , 67 , 68 ], where the Kendall rank correlation coefficient (τ) ranges from −1 to +1, and the statistical significance is tested using the p -value. For the meteorological dataset, the minimum level of significance that was adopted was α = 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…Which is a non-parametric test that does not require normally distributed data for validity [ 65 ]. This test is widely used in studies of hydrological, climatological and NDVI time series [ 65 , 66 , 67 , 68 ], where the Kendall rank correlation coefficient (τ) ranges from −1 to +1, and the statistical significance is tested using the p -value. For the meteorological dataset, the minimum level of significance that was adopted was α = 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…A pair of Landsat MSS (10 November 1972) was downloaded from the same source at the path 207/row 053 and path 207/row 054. These data are acquired for the time corresponding to the early dry season onset (October to December), enabling the clear distinction between land use/cover (LUC) types, especially agricultural fields and typical savannahs in the landscape (Traore et al, 2014;Ruelland et al, 2010).…”
Section: Mapping the Land-use And Cover For The Period 1972-2014mentioning
confidence: 99%
“…Elevation and slope can significantly influence the vegetation composition, distribution, and growth through soil moisture and fertility [68,69]. Pozzi and Small [70] and Traore et al [71] revealed a negative correlation between NDVI and population densities. However, there are some opposing views; Fuller and Gaston [14] showed that there was a long-term inverted N-shaped curve relationship between population growth and vegetation cover in a region with frequent human activities and that the influence of climate change on vegetation cover changes was relatively small.…”
Section: Discussionmentioning
confidence: 99%